Hepatocyte Endoplasmic Reticulum Stress Inhibits Hepatitis B Virus Secretion and Delays Intracellular Hepatitis B Virus Clearance After Entecavir Treatment - Chen, Huan; Mu, Maoyuan; Liu, Qichuan; Hu, Han; Tian, Caiyun; Zhang, Guoyuan; Li, Ying; Yang, Fangwan; Lin, Shide (Frontiers in Medicine, 2021)
Background: The aim of this study was to explore the effects of endoplasmic reticulum (ER) stress on hepatitis B virus (HBV) replication and the antiviral effect of entecavir (ETV). Methods: Thapsigargin (TG) and stearic acid (SA) were used to induce ER stress in HepG2.2.15 cells and HepAD38 cells that contained an integrated HBV genome, while ETV was used to inhibit HBV replication. The expression levels of glucose-regulated protein 78 (GRP78) and phosphorylated eukaryotic translation initiation factor 2 subunit alpha (eIF2α) were measured by western blotting. Intracellular HBV DNA was determined by qPCR, HBsAg by western blotting, HBV RNA by real-time RT-qPCR, and HBsAg and HBeAg in supernatants by enzyme-linked immunosorbent assay (ELISA), HBV DNA in supernatants by qPCR, respectively. Results: TG and SA induced ER stress in HepG2.2.15 cells and HepAD38 cells from 12 to 48 h post treatment. However, 4-phenylbutyric acid (PBA) partly alleviated the TG-induced ER stress. Moreover, TG inhibited HBsAg, HBeAg, and HBV DNA secretion from 12 to 48 h, while different concentrations of SA inhibited HBsAg and HBV DNA secretion at 48 h. TG promoted intracellular HBV DNA and HBsAg accumulation and the transcription of the HBV 3.5 kb mRNA and S mRNA. PBA treatment restored the secretion of HBsAg and HBV DNA. Finally, ER stress accelerated extracellular HBV DNA clearance but delayed intracellular HBV DNA clearance after ETV treatment. Conclusions: Hepatocyte ER stress promoted intracellular HBV DNA and HBsAg accumulation by inhibiting their secretion. Our study also suggested that hepatocyte ER stress delayed intracellular HBV DNA clearance after ETV treatment.